The Effectiveness of SI BANK SAM as a Solution for Waste Bank Management in Blitar Regency: Efektivitas SI BANK SAM sebagai Solusi Pengelolaan Bank Sampah di Kabupaten Blitar - Sadewo, Sadam; Hertati, Diana (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2025)
The Waste Bank Information System (SI BANK SAM) is a digital application owned by the Environmental Service of Blitar Regency that manages waste banks. This application was developed due to the suboptimal management of waste banks, which had shortcomings such as inaccurate record-keeping, slow data verification, and high operational costs. This study aims to analyze the effectiveness of SI BANK SAM in managing waste banks in Blitar Regency, enabling the Environmental Service to evaluate existing challenges. Evaluations that improve the application’s effectiveness can enhance SI BANK SAM’s role in addressing waste problems in Blitar Regency. This research uses a descriptive qualitative approach. The results show that the SI BANK SAM application is one of the best solutions provided by the Environmental Service of Blitar Regency to optimize the management of waste banks, replacing the manual system that had many drawbacks such as slow data collection and frequent discrepancies between recorded data and actual field conditions. Field findings indicate that SI BANK SAM operates as expected, with 4 out of 5 dimensions performing well based on Gibson’s (2003) effectiveness theory, which includes the dimensions of production, efficiency, satisfaction, adaptation, and development.